THE INFLUENCE OF JEOPARDY GAME TOWARDS STUDENTS’ VOCABULARY MASTERY - NOVILISA NOVILISA; SUNARA SUNARA; SUMPENA ROHAENDI (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2019)
This research is motivated by the students get difficulties in using the English vocabulary and students needed interesting technique when they learnt English. One of learning techniques that can help students understand about the material is jeopardy game. The purposes of this study are to know Jeopardy Game is influence on the students’ vocabulary mastery and the response of the students’ the learning use Jeopardy game on vocabulary mastery. This research used a quasi-experimental and the research design used is the non-equivalent pre-test post-test control group design. The Research was conducted in SMPN 1 Dawuan. The sample are VIII-A as control class and VIII-B as experiment class. The research instrument that used are test and questionnaire. The result of the research shows; the students’ response to learning by using jeopardy game got a very good category with an average was 65.85% and there is a significant influence between jeopardy game of learning towards students’ vocabulary mastery was 2.4% while the remaining 77.6% is influenced by other factors. Based on the findings, it can be concluded that the application of jeopardy game can not the influence students’ vocabulary mastery. Especially at the first grade student of SMP Negri 1 Dawuan in academic year 2018/2019.